2022
DOI: 10.13057/biodiv/d230548
|View full text |Cite
|
Sign up to set email alerts
|

Short Communication: Morphological characterization of five species of Dendrobium native to Indonesia for parent selection

Abstract: Abstract. Hartati S, Samanhudi, Cahyono O. 2022. Short Communication: Morphological characterization of five species of Dendrobium native to Indonesia for parent selection. Biodiversitas 23: 2648-2654. As one of the most plentiful orchid genera, Dendrobium has a potential genetic resource for crossing programs. Morphological characterization is an important step in determining genetic relationships among orchid species in the same genus. The research aims to identify the morphological characteristics of five s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The study in the study explained that 30 morphological characters of Dendrobium had been studied. There were 23 of the 30 morphological characters identified (76.67%) which showed various characters in flowers, leaves and roots (Hartati et al 2022). Other research explains that three types of natural orchids in the KEHATI AQUA Wonosobo Park, namely Dendrobium crumenatum, Eria retusa, and Liparis sp can be cultivated.…”
Section: Methodsmentioning
confidence: 99%
“…The study in the study explained that 30 morphological characters of Dendrobium had been studied. There were 23 of the 30 morphological characters identified (76.67%) which showed various characters in flowers, leaves and roots (Hartati et al 2022). Other research explains that three types of natural orchids in the KEHATI AQUA Wonosobo Park, namely Dendrobium crumenatum, Eria retusa, and Liparis sp can be cultivated.…”
Section: Methodsmentioning
confidence: 99%
“…According to [23], the higher the similarity score, the higher the similarity between the orchids tested. The research by [15] on five types of Dendrobium showed results at 0.80 similarities; D. lamellated and D. Anosmum had the highest similarity and a high potential to be used as elders in orchid crosses. Research by [11] on six species of Coelogyne spp.…”
Section: Introductionmentioning
confidence: 99%
“…Observations of flower morphology include flower shape, lateral dorsal sepal shape, petal shape, lateral dorsal sepal tip shape, petal tip shape, flower aroma, flowering position, number of pollinia, dorsal and lateral sepal color patterns, petal color patterns, lip callus type, lip curve position, tentacle of the labellum, and lip cross-section. According to [15], flowers are important in species identification. Based on Table 2, the observations on flower morphology show that the eight orchids observed have a round flower shape, do not have a floral scent, have a flowering position at the base, and have a number of pollinia of two.…”
Section: Introductionmentioning
confidence: 99%
“…Dendrobium mirbelianum is well-known as dark-stemmed antler orchid or mangrove orchid, which has yellow-brownish petals and sepals with slightly dark-red striped, the same color as the labellum with a white tongue in the center (Hartati et al 2022). Dendrobium nindii is known as blue orchid, relatively tall posture with slender pseudostems.…”
Section: Introductionmentioning
confidence: 99%